Eutectoid-structured WC/W2C heterostructures: A new platform for long-term alkaline hydrogen evolution reaction at low overpotentials. (February 2020) - Chen, Zhigang; Gong, Wenbin; Cong, Shan; Wang, Zhen; Song, Ge; Pan, Ting; Tang, Xueqing; Chen, Jian; Lu, Weibang; Zhao, Zhigang
Abstract: One of the major challenges encountered in hydrogen evolution reaction (HER) electrocatalysis is the development of highly-efficient catalysts suitable for use in alkaline media. Tungsten carbide-based materials have long been advocated as potential alternatives to platinum (Pt) for HER process due to their "Pt-like" electronic structures. However, they exhibit significant HER activity mostly in acid but not in alkali. Herein, we report a robust synthetic method for directly growing a unique eutectoid-structured WC/W2 C heterostructure (ES-WC/W2 C) that can serve as a highly active electrocatalyst for alkaline HER via calcination of a special two-dimensional organic-inorganic tungsten precursor. This novel ES-WC/W2 C catalyst exhibits high alkaline HER activity with an ultra-low onset-potential of 17 mV and a low overpotential of 75 mV at 10 mA/cm 2 (ɳ10 ). It yields an ultra-high exchange current density of 0.58 mA/cm 2, an enhancement of nearly 14- and 12-fold in comparison with the phase-pure WC and W2 C, respectively. Even when normalized to the electrochemically active surface area (ECSA), the normalized current density (J0, normalized ) is still significantly higher than the J0, normalized for phase-pure WC and W2 C, demonstrating the substantial improvement of intrinsic activity by constructing such heterostructures. Moreover, it also exhibits an exceptionally stability in alkaline solutions, showing no evidence of significant degradation over 480 h (>20 days) of H2 production, far exceeding the stability of other tungsten carbide-based electrocatalysts. To the best of our knowledge, this is the first time such a eutectoid-structured material has been reported to efficiently catalyze the HER in alkaline solution. Graphical abstract: WC/W2 C heterostructures with eutectoid-structured interface are directly synthesized via pyrolysising a special organic-inorganic tungsten precursor. This novel electrocatalyst exhibits an excellent HER activity in both acidic and alkaline solutions, and can be stable for over 480 h towards alkaline HER process. Image 1 Highlights: The quick and low diffusion of carbon atoms are purposely introduced in our synthesis. The as-obtained eutectoid-structured WC/W2 C heterostructures can exhibit high alkaline HER activity with a low overpotential of 75 mV at 10 mA/cm 2 . The DFT calculations suggest the eutectoid-structured heterostructures should be responsible for the enhanced alkaline HER activity and stability.